CLUSTERING IN WIRELESS SENSOR NETWORK: A REVIEW (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
WSNs are evolving as both a vital new domain in the IT environment and a hot research including system design, networking, and distributed algorithms, programming models, data management, security and social components. Wireless sensor networks are rapidly picking up the popularity as they are potentially low cost solutions. The fundamental thought of sensor network is to scatter minor sensing gadgets over a particular geographic zone for some specific purposes like target tracking, surveillance, environmental screening and so on. These tiny devices are equipped for sensing a few progressions of parameters and communicating with different units. Since the network is wireless, the nodes communicate with each other via means of wireless. The wireless sensor network is interfaced with the outside world by a gateway server or controlling server. This paper focuses on the detailed survey of various clustering approaches used in wsn.